Studi Mikrogravitas di Bukit Tambun, Tambun, Ipoh, Perak, Malaysia - Elsa Kardiana (Universitas Syiah Kuala, Banda Aceh, 2025)
A Microgravity survey was conducted in Bukit Tambun, Tambun, Ipoh to delineate subsurface geological structures, particularly cavities and rock boundaries. A total of 121 gravity measurements were acquired and processed to generate a Bouguer anomaly map. Further filtering and interpretation were carried out using several geophysical techniques, including Low Pass Filter (LPF), High Pass Filter (HPF), Total Horizontal Derivative (THD), and 3D Euler Deconvolution. The Bouguer anomaly map revealed low anomalies concentrated in the southeast and west, indicating thick sediment zones, while high anomalies in the north suggest the presence of bedrock, mainly limestone and granite. THD analysis showed dominant fault trends in a southeast–northwest orientation. The 3D Euler Deconvolution identified three potential cavity zones at depths ranging from 12 to 43 meters and fault structures between 4 and 39 meters. Subsurface modeling using 2D profiles confirmed the existence of three major lithological layers: alluvium, limestone, and granite, with almost vertical contacts. Rounded to semi-spherical low-anomaly zones observed in the models are interpreted as sediment-filled cavities or depressions, possibly indicating sinkhole development. These findings contribute to understanding the geohazard potential and structural framework of the study area. Abstrak Studi Mikrogravitas dilakukan di Bukit Tambun, Tambun, Ipoh untuk mengidentifikasi struktur geologi bawah permukaan, terutama keberadaan rongga dan batas batuan. Sebanyak 121 titik pengukuran gravitasi dikumpulkan dan diolah untuk menghasilkan peta anomali Bouguer. Data kemudian dianalisis menggunakan beberapa teknik geofisika, termasuk Low Pass Filter (LPF), High Pass Filter (HPF), Total Horizontal Derivative (THD), dan 3D Euler Deconvolution. Peta anomali Bouguer menunjukkan anomali rendah di bagian tenggara dan barat yang mengindikasikan zona sedimen tebal, sedangkan anomali tinggi di utara menunjukkan keberadaan batuan dasar, terutama batu kapur dan granit. Analisis THD memperlihatkan pola sesar dominan berarah tenggara–barat laut. 3D Euler Deconvolution mengidentifikasi tiga zona rongga potensial pada kedalaman 12 hingga 43 meter serta struktur sesar pada kedalaman 4 hingga 39 meter. Pemodelan bawah permukaan melalui profil 2D menunjukkan keberadaan tiga lapisan utama: aluvium, batu kapur, dan granit, dengan batas yang hampir vertikal. Zona anomali rendah berbentuk bulat hingga semi-sferis dalam model ditafsirkan sebagai rongga atau zona depresi yang terisi sedimen, yang kemungkinan menunjukkan perkembangan sinkhole. Temuan ini memberikan kontribusi terhadap pemahaman potensi bahaya geologi dan kerangka struktur geologi wilayah studi.